Screening the Olive Tree Phyllosphere: Search and Find Potential Antagonists Against Pseudomonas savastanoi pv. savastanoi - Mina, Diogo; Pereira, José Alberto; Lino-Neto, Teresa; Baptista, Paula (Frontiers in Microbiology, 2020)
Olive knot (OK) is a widespread bacterial disease, caused by Pseudomonas savastanoi pv. savastanoi (Pss), which currently has not effective control methods. The use of naturally occurring microbial antagonists, such as bacteria, as biocontrol agents could be a strategy to manage this disease. The objective of this work was to select bacteria from olive tree phyllosphere able to antagonize Pss using in vitro and in planta experiments. The elucidation of their modes of action and the potential relationship between antagonism and bacteria origin has been investigated, as well. To this end, 60 bacterial isolates obtained from the surface and inner tissues of different organs (leaves, twigs and knots), from two olive cultivars of varying susceptibilities to OK, were screened for their in vitro antagonistic effect against Pss. A total of 27 bacterial strains were able to significantly inhibit Pss growth, being this effect linked to bacteria origin. Strains from OK-susceptible cultivar and colonizing the surface of plant tissues showed the strongest antagonistic potential. The antagonistic activity was potentially due to the production of volatile compounds, siderophores and lytic enzymes. Bacillus amyloliquefaciens P41 was the most effective antagonistic strain and their capacity to control OK disease was subsequently assayed using in planta experiments. This strain significantly reduces OK disease severity (43.7%), knots weight (55.4%) and population size of Pss (26.8%), while increasing the shoot dry weight (55.0%) and root water content (39.6%) of Pss-infected olive plantlets. Bacterial isolates characterized in this study, in particular B. amyloliquefaciens P41, may be considered as promising biocontrol candidates for controlling OK disease.